Exploring effects of gut microbiota on tertiary lymphoid structure formation for tumor immunotherapy - Liu, Yuqing; Li, Fan; Wang, Juanjuan; Yang, Rongcun (Frontiers in Immunology, 2025)
Anti-tumor immunity, including innate and adaptive immunity is critical in inhibiting tumorigenesis and development of tumor. The adaptive immunity needs specific lymph organs such as tertiary lymphoid structures (TLSs), which are highly correlated with improved survival outcomes in many cancers. In recent years, with increasing attention on the TLS in tumor microenvironment, TLSs have emerged as a novel target for anti-tumor therapy. Excitingly, studies have shown the contribution of TLSs to the adaptive immune responses. However, it is unclear how TLSs to form and how to more effectively defense against tumor through TLS formation. Recent studies have shown that the inflammation plays a critical role in TLS formation. Interestingly, studies have also found that gut microbiota can regulate the occurrence and development of inflammation. Therefore, we here summarize the potential effects of gut microbiota- mediated inflammation or immunosuppression on the TLS formation in tumor environments. Meanwhile, this review also explores how to manipulate mature TLS formation through regulating gut microbiota/metabolites or gut microbiota associated signal pathways for anti-tumor immunity, which potentially lead to a next-generation cancer immunotherapy.